Strong morphological defects in conditional Arabidopsis abp1 knock-down mutants generated in absence of functional ABP1 protein [version 1; referees: 1 approved, 2 approved with reservations] - Jaroslav Michalko; Matouš Glanc; Catherine Perrot-Rechenmann; Jiří Friml (F1000Research, 2016)
The Auxin Binding Protein 1 (ABP1) is one of the most studied proteins in plants. Since decades ago, it has been the prime receptor candidate for the plant hormone auxin with a plethora of described functions in auxin signaling and development. The developmental importance of ABP1 has recently been questioned by identification of Arabidopsis thaliana abp1 knock-out alleles that show no obvious phenotypes under normal growth conditions. In this study, we examined the contradiction between the normal growth and development of the abp1 knock-outs and the strong morphological defects observed in three different ethanol-inducible abp1 knock-down mutants (abp1-AS, SS12K, SS12S). By analyzing segregating populations of abp1 knock-out vs. abp1 knock-down crosses we show that the strong morphological defects that were believed to be the result of conditional down-regulation of ABP1 can be reproduced also in the absence of the functional ABP1 protein. This data suggests that the phenotypes in abp1 knock-down lines are due to the off-target effects and asks for further reflections on the biological function of ABP1 or alternative explanations for the missing phenotypic defects in the abp1 loss-of-function alleles.